The Business of Last Chance Tourism: Stakeholders' Perspectives - Swartman, Bobbie (University of Waterloo, 2015)
Last Chance Tourism (LCT) is argued as a new form of travel behaviour emerging because of climate change. Some tourism stakeholders and communities have already begun adapting to climate changes they have experienced. Therefore, the purpose of this research was to explore the dynamics between climate change and business planning of tourism stakeholders at two chosen case study sites, the Athabasca Glacier in Jasper National Park and Polar Bear tourism at Churchill, Manitoba. This research focused on understanding climate change perceptions, adaptation strategies, and marketing efforts of stakeholders at the study sites. The research used mixed methods approach with an interpretive paradigm for analysis. This study conducted semi structured interviews with 17 participants from the study sites, 10 from Jasper National Park, and seven from Churchill, Manitoba. In addition to interviews, 20 stakeholder websites from each study site were analyzed to understand how images play a role in branding. The results revealed that climate change is and will pose challenges for stakeholders. The majority of participants, 56%, were either moderately or extremely concerned about climate change. This research confirms and adds detail to previous studies on adaptations and LCT. Many of the participants thought LCT had negative implications, with only two participants suggesting they would think about using it as a marketing technique. Participants have already been making adaptations due to environmental changes, and believe they will adapt when necessary in the future. While only 47% of participants said they have a marketing strategy for their specific destination, the analysis of the 40 websites revealed the chosen websites use images of the Athabasca Glacier or polar bears for a majority of website images. While this exploratory study was important to understand stakeholder perceptions at each location, future studies need to examine both adaptive capacity and ethical implications of marketing LCT more in depth. Marketing LCT ...